University and society in Peru: meetings and disagreements - Murrugarra Florián, Edmundo (2008)
The university is the space to think and rethink the problems of human coexistence. The reform of the university in the first half of the 20th century did not raise the question of internal coloniality. In the second half there was a disagreement. The new university leaders were not prepared to assume their functions. The university crisis became extreme in the eighties. As a result, the public university does not have a research proposal.